2019
DOI: 10.1007/s12561-019-09237-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Temporal Variation in Physical Activity Using Functional Principal Components Analysis

Abstract: Accelerometers are person-worn sensors that provide objective measurements of movement based on minute-level activity counts, thus providing a rich framework for assessing physical activity patterns. New statistical approaches and computational tools are needed to exploit these densely sampled time-series data. We implement a functional principal component mixed model approach to ascertain temporal activity patterns in 578 overweight women (60% cancer survivors) and summarize individual patterns with unique pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…A few studies investigated diurnal patterns of PA (data collected over 5-7 days) and health [64][65][66][67]. Distinct temporal PA patterns observed in this study have been detected by two other studies that used kmeans and x-means clustering approaches to derive clusters using overall activity measured by metabolic equivalent of tasks (METs) and timing of PA [64,65].…”
Section: Discussionsupporting
confidence: 51%
“…A few studies investigated diurnal patterns of PA (data collected over 5-7 days) and health [64][65][66][67]. Distinct temporal PA patterns observed in this study have been detected by two other studies that used kmeans and x-means clustering approaches to derive clusters using overall activity measured by metabolic equivalent of tasks (METs) and timing of PA [64,65].…”
Section: Discussionsupporting
confidence: 51%
“…We identified a few studies that examined diurnal patterns of PA/ SB, (i.e., patterns based on the time of day that active/ sedentary time was accumulated) and health. Using functional principal components analysis, Xu et al reported that higher evening (vs mid-day) activity was associated with worse mental quality-of-life [26]. Zeitzer et al found principal components-derived patterns that were predictive of changes in sleep and cognition, as well as cardiovascular-related mortality and all-cause mortality [63].…”
Section: Discussionmentioning
confidence: 99%
“…At study entry, mean (SD) daily sedentary time and MVPA were respectively 597 (103), and 50 (34) minutes. Mean (SD) physical functioning scores at baseline were 69 (26).…”
Section: Study Sample and Baseline Descriptive Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As physical activity varies substantially over the course of a week [37,38], an observational study design was considered appropriate to investigate the daily relationship of physical activity and sleep quality in individuals suffering from RLS. Both physical activity levels and sleep quality of a given individual vary over the course of a week [39]. Thus, the co-variation between physical activity during the day and quality of sleep during the subsequent night should be taken into account.…”
Section: Study Design and Recruitmentmentioning
confidence: 99%